New Adjusted Cutoffs for "Normal" Endocardial Voltages in Patients With Post-Infarct LV Remodeling - Sramko, Marek; Abdel-Kafi, Saif; van der Geest, Rob J; de Riva, Marta; Glashan, Claire A; Lamb, Hildo J; Zeppenfeld, Katja (JACC. Clinical electrophysiology, 2019)
OBJECTIVES: This study sought to determine new reference cutoffs for normal unipolar voltage (UV) and bipolar voltage (BV) that would be adjusted for the LV remodeling. BACKGROUND: The definition of "normal" left ventricular (LV) endocardial voltage in patients with post-infarct scar is still lacking. The reference voltage of the noninfarcted myocardium (NIM) may differ between patients depending on LV structural remodeling and the ensuing interstitial fibrosis. METHODS: Electroanatomic voltage mapping was integrated with isotropic late gadolinium-enhanced cardiac magnetic resonance in 15 patients with nonremodeled LV and 12 patients with remodeled LV (end-systolic volume index >50 ml/m2 with ejection fraction <47% assessed by cardiac magnetic resonance). Reference voltages (fifth percentile values) were determined from pooled NIM segments without late gadolinium enhancement. RESULTS: The cutoffs for normal BV and UV were ≥3.0 and ≥6.7 mV for nonremodeled LV and ≥2.1 and ≥6.4 mV for remodeled LV. Endocardial low-voltage area (LVA) defined by the adjusted cutoffs corresponded better to late gadolinium enhancement-detected scar than did LVA defined by uniform cutoffs. In 15 patients who underwent successful ablation of ventricular tachycardia, the LVA contained >97% of targeted evoked delayed potentials. Insights from whole-heart T1 mapping revealed more fibrotic NIM in patients with remodeled LV compared with nonremodeled LV. CONCLUSIONS: This study found substantial differences in endocardial voltage of NIM in post-infarct patients with remodeled versus nonremodeled LV. The new adjusted cutoffs for "normal" BV and UV enable a patient-tailored approach to electroanatomic voltage mapping of LV.
Keywords: Magnetic Resonance Imaging; Female; Electrophysiologic Techniques, Cardiac; endokard; elektrofyziologické techniky kardiologické; Tachycardia, Ventricular; ženské pohlaví; jizva; Catheter Ablation; lidé; magnetická rezonanční tomografie; magnetická rezonance kinematografická; katetrizační ablace; studie případů a kontrol; referenční hodnoty; Magnetic Resonance Imaging, Cine; Ventricular Remodeling; Cicatrix; Male; Case-Control Studies; Aged; Reference Values; komorová tachykardie; remodelace komor; Myocardial Infarction; Endocardium; lidé středního věku; senioři; mužské pohlaví; Middle Aged; infarkt myokardu; Humans